Inequalities for Riemann–Liouville Fractional Integrals of Strongly s,m-Convex Functions - Fuzhen Zhang; Ghulam Farid; Saira Bano Akbar (Journal of Mathematics)
The results of this paper provide two Hadamard-type inequalities for strongly s,m-convex functions via Riemann–Liouville fractional integrals and error estimations of well-known fractional Hadamard inequalities. Their special cases are given and connected with the results of some published papers.